THE SOCIAL CONFLICT AND EDUCATIONAL VALUES IN THE SHORT STORY COLLECTION LELAKONE SI LAN MAN BY SUPARTO BRATA - Endah Nurhidayah; Widiyono, Yuli; Setyowati, Herlina (Department Javanese Literature and Language Education in Collaboration with Faculty of Teacher Training and Education Muhammadiyah University of Purworejo, 2025)
The purpose of this research is to describe social conflicts and educational values found in the short story collection Lelakone Si lan Man by Suparto Brata. The discussion of social conflicts applies Lewis A. Coser's theory, and the analysis of educational values uses Andri Wicaksono's theoretical concept. This research falls under the category of qualitative descriptive research. In this study, data collection techniques used include observation and note-taking. The research instrument is the researcher themselves, with additional instruments such as data recording cards. The analysis technique employed in this study is qualitative descriptive with a literary sociology approach. The results of the analysis indicate that: (1) The social conflicts found in the short story collection can serve as a reference for behavior, aiming to prevent harmful conflicts. (2) The educational values in the short story collection are reflected in the good and bad behavior of the characters. Good behavior can serve as a model to be applied in life, while bad behavior should be avoided. Such behaviors are often found in social life.